INFLUENCE OF HONEY-ROASTING ON THE MAIN PHARMACOLOGICAL ACTIVITIES AND THE WATER-SOLUBLE ACTIVE GLYCOSIDES OF LICORICE - Wang, Mengyue; Zhang, Min; Tang, Qiyu; Li, Xiabo (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
In traditional Chinese medicine (TCM), licorice is usually processed with honey and traditionally used in decoction form. However, the influence of honey-roasting on the main pharmacological activities and the water-soluble active constituents of licorice has not been reported. The aim of the present study is to determine whether honey-roasting can modify the main pharmacological activities and the active constituents of licorice. According to licorice clinical application and processing method, the mainly related pharmacological activities of crude licorice, processed licorice and refined honey, such as enhancing immune function, relieving cough, eliminating phlegm and detoxication, were compared. The results showed that honey-roasting obviously reinforced the licorice activity of enhancing Pi-deficiency mice’s immune function, and significantly weaken the licorice activity of relieving cough, removing phlegm and detoxication. However, honey didn’t show the significant activity of relieving cough, removing phlegm and detoxication. The influence of honey-roasting on the chemical compositions in licorice slice and licorice decoction was investigated by using HPLC. The results showed that the content and the decocting quantity of mainly 5 active glycosides in licorice, i.e. liquiritin apioside, liquiritin, licuraside, isoliquiritin and glycyrrhizin, obviously changed after processing; glycyrrhizin and liquiritin obviously decomposed during honey-roasting. In conclusion, honey-roasting obviously modified the main pharmacological activities and the water-soluble compositions of licorice. The modification was not cause by honey only. This finding may shed some light on understanding the differences in the therapeutic values of crude and processed licorice.